(untitled) (Journal of the College of Basic Education, 2024)
This research aims to find out (the role of the teacher in active learning). To achieve the goal of the research, the researcher intended to explain the role of the teacher in active learning by dividing the research into chapters that dealt with aspects of the role of the teacher in active learning. After that, it is one of the elements of the education process, so it has a distinctive and effective role during the application. Active learning is based on the roles determined by the theoretical frameworks of the constructivist theory and the social theory of learning. Therefore, a number of researchers and specialists have recommended that the teacher exercise the following roles to ensure the success of active learning and achieve its desired goals. The researcher found many roles for the teacher in active learning, including providing guidance, guidance and assistance to the learners during learning, Putting learners in situations that stimulate thinking and make them feel challenged and determined, increase learners’ motivation and develop their inclinations and attitudes towards learning, and conclude the application of teaching strategies that have proven effective in increasing students’ interaction with the educational material, their interest in acquiring information and new types of knowledge, and applying teaching strategies that focus on cooperation and active participation during learning. This may help students cooperate in achieving goals collectively.